Democratic Decentralisation and Traditional Authority: Dilemmas of Land Administration in Rural South Africa - Ntsebeza, Lungisile (European journal of development research, 2004)
Post-apartheid South Africa embarked on an important democratisation process that included reforms in local government and land administration in the former Bantustans. A new conception of "developmental local government" introduced the notion of elected local leadership and an emphasis on improving the quality of life of previously disadvantaged sectors. Nevertheless, this democratisation process risks serious compromise due to the concessions being made to traditional rural authorities - the same autocratic local authorities who enjoyed significant powers under apartheid. In particular, the legal transfer of land administration to elected officials has not occurred, leaving this important power under the authority of unaccountable local chiefs and headmen. Is democratic decentralisation compatible with the traditional authorities (chiefs of various ranks) who inherit their posts? While some chiefs and headmen may choose to promote local participation, the freedom to choose one's leaders is automatically excluded - seriously limiting downward accountability. This contribution argues that the central government must recognise this incompatibility and support the rights of rural residents to full citizenship. (Original abstract)